Photocatalytic Degradation of Diazinon Using Titanium Oxide Synthesized by Alkaline Solvent - Mohammad Rofik Usman; Atiek Rostika Noviyanti; Diana Rakhmawaty Eddy (Indonesian Journal of Chemistry, 2017)
Photoactivity of titanium dioxide (TiO2) can be improved by turning it into nanoparticles. Synthesis of TiO2 nanoparticles can be done by using hydrothermal method. Hydrothermal method is influenced by types of precursor, hydrothermal conditions, including time, temperature, type and concentration of reactants. The purpose of this study is to obtain a hydrothermal condition which produces crystals of TiO2 nanoparticles with high quality. The material used was titanium tetrachloride (TiCl4) as initial precursors and for the type of reactants was used aqudestilate, aquabidestilate, ethanol, t-butanol, sodium hydroxide (NaOH) and potassium hydroxide (KOH). The resulting diffractogram showed the crystal structure of TiO2 nanoparticles with anatase and rutile. Based on calculations using the scherrer equation, TiO2 crystal obtained had a crystal size below 50 nm in both anatase and rutile. The percentage of rutile and anatase composition was obtained by using rietveld method with the help of rietica software. Morphology of TiO2 anatase showed particles with shape of cubic, while rutile was flower-shaped.